Automatic recovery unit of power plant demineralized water - CHENG SHOUQING; WANG FANG (2015)
The utility model relates to an automatic recovery unit of power plant demineralized water. It includes to come the water pipe, the control valve, the filter, the bleeder line, the drain pipe, the oral siphon, the outlet pipe, a main bod, the core vent, the control water tank, control water tank dress is in main part one side upper end, come water piping connection in main part one side upper end, go out water piping connection main part one side upper end, the upper end is equipped with and is equipped with the bleeder line on filter and the tank wall in the middle of main part and the tank wall of control between the water tank, the inside lower extreme of control water tank is equipped with the control valve, the oral siphon upper end is connected to the control valve lower extreme, oral siphon lower extreme connection subject lower extreme, control water tank outside lower extreme is equipped with the drain pipe, a plurality of core vents are equipped with to the main part upper end, exit linkage condenser one side of outlet pipe. The advantage is that the design is simple, convenient to use, and simple structure is compact, and the equipment is convenient, and the demineralized water that can make thermal power plant parts such as present thermal power factory and nuclear power plant discharged can be retrieved to reduce power plant's demineralized water moisturizing rate, practiced thrift valuable water resource.